ASPEK HUKUM PERLINDUNGAN TENAGA KERJA WANITA SEKTOR UMKM DI KOTA MEDAN - Zuhriati Khalid (Penelitian dan Pengembangan Ilmu, 2024)
Law as a means of controlling social behavior in society was created to fulfill a sense of security, comfort, welfare and justice in daily social interactions in the community. Therefore a legal strategy is needed in order to create universal legal protection. This universal protection is contained in various laws and regulations in Indonesia. However, the implementation of regulations contained in various forms of legislation that should provide universal legal protection has not been implemented as expected, one of which is the lack of attention regarding the protection of female workers who work in the UMKM sector, especially in Medan City. This research aims to examine various forms of legal instruments, both international and domestic which regulate legal protection for female workers, and see the extent to which the relevant factions have done so that the effectiveness of these legal instruments can truly provide universal protection, especially for women workers. female workers whose source of income comes from the UMKM sector in the city of Medan. The qualitative method in this research is used by using the basic concept of law, the essential of various statutory rules, and dogmas that can produce solutions in this study. The results of this research indicate that in its implementation of legal protection for female workers, especially in the UMKM sector in the city. Medan is still far from expectations, it can be seen from the emergence of various cases in the community related to female labor. However, in order to overcome this problem, Indonesia actually has various legal instruments, both national and international, which are contained in various laws and regulations that have even existed since the period of the kingdom until now. In order to fulfill legal protection for female workers in the UMKM sector, especially in the city of Medan, it involves many related parties, such as the Government, Employers / Associations, NGOs (Non-Government Organizations) and the community. The efforts made by these parties are essentially the implementation of various forms of policies and programs related to the supervision and implementation of protection for female workers, especially in the UMKM sector.